1997
DOI: 10.1164/ajrccm.155.1.9001318
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of DLCO for hemoglobin concentration.

Abstract: The equation proposed by Cotes and coworkers is currently considered as the most acceptable to correct carbon monoxide diffusing capacity (DLCO) for hemoglobin concentration [Hb] by both the American Thoracic Society (ATS) and the European Respiratory Society (ERS) guidelines for standardization of DLCO. In a previous study on 24 anemic patients undergoing bone marrow transplantation (1), we found that DLCO is underestimated using the equation of Cotes and coworkers. To further explore this finding, 28 anemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Since CO-Hb binding is such an important factor in CO transfer, DL,CO changes can be substantial as a function of Hb concentration [93][94][95][96][97]. The empirical change in DL,CO with Hb change closely matches what is expected from a theoretical approach using the relationship in equation 2, with h assumed to be proportional to the Hb, DM/hVc is assumed to be 0.7 [96], and the ''standard'' Hb value is assumed to be 14.6 g?dL -1 (9 mmol?l The equation for adjusting predicted DL,CO in children ,15 yrs of age and females is: DL,CO,predicted for Hb~DL,CO,predicted|(1:7 Hb=(9:38zHb)) ð14Þ…”
Section: Adjustment For Haemoglobinmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CO-Hb binding is such an important factor in CO transfer, DL,CO changes can be substantial as a function of Hb concentration [93][94][95][96][97]. The empirical change in DL,CO with Hb change closely matches what is expected from a theoretical approach using the relationship in equation 2, with h assumed to be proportional to the Hb, DM/hVc is assumed to be 0.7 [96], and the ''standard'' Hb value is assumed to be 14.6 g?dL -1 (9 mmol?l The equation for adjusting predicted DL,CO in children ,15 yrs of age and females is: DL,CO,predicted for Hb~DL,CO,predicted|(1:7 Hb=(9:38zHb)) ð14Þ…”
Section: Adjustment For Haemoglobinmentioning
confidence: 99%
“…Results from a more recent study in patients with a wide range of Hb abnormalities [97] showed a slightly greater and more In these calculations, room temperature (T) is measured in Celsius and gas pressures are measured in mmHg. In all four cases, the inspired volume (VI) is the measured volume of inhaled dry gas and, thus, is considered under ambient temperature, ambient pressure, and dry (ATPD) conditions.…”
Section: Adjustment For Haemoglobinmentioning
confidence: 99%
“…The patients' chest radiographs and standard pulmonary function tests were within normal limits, except for a slight reduction in carbon monoxide diffusing capacity which averaged 78.5% of predicted after adjustment for haemoglobin concentration [15]. Their electrocardiogram, echocardiogram, and radionuclide ejection fraction were all consistent with a normal systolic function of the allograft.…”
Section: Study Populationmentioning
confidence: 78%
“…[3][4][5][6][8][9][10]14,16,18 This study was done with current equipment and procedures and good test quality, giving comparable results across several cities of Latin America with substantial advantages over previous studies. Reference equations in use were obtained many years ago with varied equipment, procedures, and populations and according to our data give results with systematic bias for single-breath D LCO and also with coefficients that do not adjust properly to changes with age, altitude, and height.…”
Section: Discussionmentioning
confidence: 99%